The role of touch in osteopathic practice: A narrative review and integrative hypothesis. (February 2021) - Baroni, Francesca; Ruffini, Nuria; D'Alessandro, Giandomenico; Consorti, Giacomo; Lunghi, Christian
Abstract: Introduction: Osteopathy relies on a touch-based approach to promote health. This narrative review aims to analyze the role of touch in clinical osteopathic practice. Methods: A database search was conducted using MEDLINE, EMBASE, PEDro and Google Scholar. Peer-reviewed papers without specifying limits on dates and design were included. Results: 47 articles met the inclusion criteria and were used to elucidate two main themes: Biological and psychological effects of touch; Touch in the context of osteopathic clinical reasoning. Discussion: Touch is one of the tools to achieve a collaborative interaction with the patient, to substantiate clinical information, and to detect somatic dysfunctions: neuro-myofascial active areas that might act as an osteopath-patient interface to transmit the biological and physiological effects of touch. Conclusion: The findings of the review support a shared decision-making process, in which touch is one of the osteopath-patient dyad 's leading communication tools to develop a tailor-made osteopathic approach. Highlights: Touch is a therapeutic and communication skill aimed to tailor the osteopathic approach. Touch drives osteopathic clinical reasoning. Touch is able to elicit a number of biological and physiological effects on tissue. It is important to determine the accuracy of touch-based diagnostic procedures in the osteopathic decision-making process. The present review proposed a framework for a shared decision-making process that can be applied in clinical practice.